Карпатський єврорегіон у контексті євроінтеграційних планів України - Химинець, В.В. (Економіка природокористування і охорони довкілля, 2013)
У статті проаналізовано сучасний стан співпраці між Україною та державами Європейського Союзу в рамках створеного ними Карпатського єврорегіону, визначено проблеми, що заважають успішній євроінтеграції України, та її перспективи. In recent decades, Ukraine wants to get closer to the European economic and social standards. Promotion of Ukraine towards to European integration and granting a new status to relations of Ukraine and European Union depends on implementation of consistent and balanced reforms in economic and social spheres, process efficiency of approximation of Ukrainian legislation to EU legislation, the implementation of the Agreement on Partnership and Cooperation between Ukraine and the EU and its Member States.
In this work analyzes the results of cooperation between participation countries in the Carpathian Euroregion, on this basis proposed the new mechanisms to solve existing problems and promote integration processes to the east.
This work (on example of Carpathian Euroregion) shows that Euroregions as one of organizational form of cross-border relations can develop special comprehensive programs of economic, cultural and humanitarian cooperation, implement specific cross-border economic projects and thus positively affects the Ukrainian’s European integration plans.
The author insist that Ukraine which until now only passively received financial assistance which single out by EU and lobbied neither their priorities nor the amount of aid has changed this approach and strongly state its intentions towards European integration and demonstrate the capacity to reform. Excluding national priorities the highlighted EU resources do not always allow you to realize the planned results.